Prevalence of acute bronchiolitis in the NGMCTH Kohalpur - Gupta, MM; Khetan, S (Devdaha Medical Journal, 2026)
Introduction: Acute bronchiolitis, a common respiratory condition in infants and young children, is a leading cause of hospitalization for respiratory infections. The illness typically starts with upper respiratory symptoms before progressing to wheezing and breathing difficulties. In developing regions, limited healthcare access may lead to delays in diagnosis and treatment. Environmental and socio-demographic factors, including exposure to smoke, air pollution, and nutritional status, can influence the incidence and severity of bronchiolitis. This study aims to assess the prevalence, clinical features, and risk factors of acute bronchiolitis in children under two years old at Nepalgunj medical college teaching hospital.Methods: This observational study included 93 clinically confirmed cases of acute bronchiolitis based on the National Institute for Health and Care Excellence guidelines. Data were collected on socio-demographic variables, clinical features, nutritional status, and environmental risk factors. Data analysis was done for descriptive statistics, such as mean, Standard deviation, median, range, and percentage. The data were analysed with IBM SPSS Statistics version 26, and the chi-square test was used.Results: The prevalence of acute bronchiolitis was 23.97%. Most cases occurred in infants aged 1-6 months (57%), and a male predominance of 69.9% was noticed. Common symptoms included cough and nasal congestion (100%), rapid breathing (90.3%), and chest retractions (57%). Fever was present in 43% of cases, while feeding difficulties were noted in 32.3%. Nutritional assessments revealed that 60.21% of infants had normal birth weights. Environmental exposures indicated that 32.25% of families had smoked, and 48.4% of cases were associated with indoor air pollution.Conclusion: The findings of this study underscore the high prevalence of acute bronchiolitis in young children, particularly in infants under one year of age. The study highlights the importance of early diagnosis and intervention to mitigate the disease's impact on respiratory health.